Implicações jurídicas do trabalho doméstico no Brasil - Rabelo, Janaina da Silva (2015)
Domestic work is one of the oldest professions existing in Brazilian society, being historically linked to slavery and colonialism, which contributes to the non-recognition of the historical and social importance of these subjects and also with the scant legal protection. It is a non-economic activity, labor achievements have been made with difficulties, that why is prejudice and devaluation within the society. Until recently excluded from the CLT protection, for long time domestic servants were protected by Law N. 5.859/72, which guaranteed the only record in the CTPS, the right to leave and social security. The Federal Constitution of 1988 expanded the list of labor rights to domestic category, but kept the situation of inequality between domestic and other urban and rural workers. After 1988, some bills were presented to Congress in order to extend rights until not guaranteed by the Constitution. Discussions on the legislative culminated in the presentation of the Proposed Constitutional Amendment N. 478/2010 in the House, which had its submissions to the drop-down principle, for the achievement of certain rights, such as FGTS, would increase the financial burden on household employers. Only after the adoption of the Convention on Decent Work for Workers and Domestic Workers of the International Labor Organization (No. 189), debates in Congress resumed on extending the list of labor rights to domestic, which ended in the promulgation Constitutional Amendment N. 72, on April 02, 2013. However, considering that some rights are not self-administered and are striving for legal regulation approved the Supplementary Law No. 150/2015 in order to minimize the legal uncertainty framework and also of operational difficulties of the 'new' rights in the domestic labor everyday. Finally, this change in the legal system is essential for the recognition and appreciation of domestic work as a builder and developer of the economy and society. The research is based on descriptive and explanatory methods and draws on research in bibliographic and documentary data. The research is based on descriptive and explanatory methods and draws on research in bibliographic and documentary data.